MACAO’S NONGAMING ENTERTAINMENT, CULTURE AND CITY BRANDING - Carlos Siu Lam; Lynn Jamieson (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Although entertainment can be a pull-factor to attract tourists in their trips, it can be easily duplicated in other jurisdictions. Focused on the non-gaming entertainment by the gaming concessionaires in Macao, this paper examines the entertainment development, and explores how these concessionaires identify the right entertainment for patrons and the challenges associated with such entertainment offerings. Despite Macao’s wealth of East-West culture, this study analyzes the use of such culture in Macao’s entertainment, and the creation of its unique branding. The integration of culture into such entertainment, when coupled with Macao’s smallness, may represent the essential factors to satisfy tourists’ multiple needs for entertainment products, thereby leading to Macao’s renewed branding as a center of tourism and leisure from its strong gaming image. This study is one of a few that focuses on the merger of culture and entertainment, and is exploratory and qualitative in nature. Semi-structured in-depth interviews with executives in Macao’s entertainment segment were utilized. Such interview findings were analyzed using the Miles and Huberman (1994) framework, along with the data from the annual reports of the concessionaires and the Macao Census and Statistics Service. The findings may be useful for gaming destinations planning to alter their branding.